Broccoli’s production in the agroindustry of Mexico and its competitiveness in the international market - Cisneros Reyes, Y. D.; Rocha Ibarra, Jesús Ernesto (Acta Universitaria, 2019)
This paper analyses in a quantitative way the broccoli’s production of Mexico and its competitiveness compared to the leaders in the international market during the past decade. The considered factors are production volume, exports, imports, production cost, consumption and others. The used methodology is that proposed by Vollrath (1991) who created an index to measure the competitive advantage of agricultural products of different countries. From the results, it is interpreted that the Mexican producers of broccoli, especially those located in the Bajio area, have potential.